The Role of Cultural & Heritage Destination Branding in the Economic Development of Jaunsar Bawar – A Tribal Region of Himalayas - Chauhan, Himanshu (The journal of contemporary issues in business and government, 2021)
Purpose: Cultural & Heritage Destination Branding plays an important role to attract tourists. Jaunsar Bawar is endowed with historical and archaeological sites. The main purpose of this study is to identify the constituent elements of the overall image of the brand of Jaunsar Bawar’s main heritage destinations by utilizing heritage, general, and unique images, and it proposes a model for branding Jaunsar Bawar’s cultural & heritage destinations. The region has all the potential to be an important cultural heritage destination in the world. Well-planned branding strategies of these heritage destinations are a primary requirement to attract both foreign and domestic tourists. There are some barriers, which can impede successful heritage tourism marketing in Jaunsar Bawar. Lack of coordination among stakeholders, insufficient funding and providing less importance to the needs of the tourists can obstruct successful heritage destination branding. Developing creative promotional program, coordination among relevant stakeholders, conservation and protection of heritage sites and active participation of both private and public sector are necessary to implement heritage destination branding in Jaunsar Bawar. Design/methodology/approach – This research is exploratory in nature and it uses the qualitative approach of primary research methodology by adopting a non-random stratified sampling method. To collect the data, approach of face-to-face semi-structured & open-ended interviews of 20 local people of Jaunsar from varied background were conducted. Outcomes – The study reveals that the people perceive Destination Branding as an effective tool for the enhancement of the tourism in field related to Cultural & Historical perspective of a tribal region like Jaunsar Bawar. The study also establishes that the various initiatives in field of creating a destination brand enhances the reputation and build a very strong, unique & competitive brand in the minds of locals as well as in the minds of tourists/ visitors who are planning or who have visited Jaunsar Bawar and this could result in the economic development of this Himalayan tribal region. Research implications – The findings of the study represent a significant contribution to the field of destination branding and will help practitioners to develop destination brand of their area of research and achieve competitive advantage in long-run which will create several business opportunities in the local area and thus gives competitive advantage in the long-run. Research limitations – The study is confined only to the region of Jaunsar Bawar thus having a limited geographic scope of one region of one state of India. Therefore, further research may be carried out by studying other tribal regions of Himalayas.